Let F be the field of complex numbers and let T be the function from F
3
into F
3 defined by
T(x1, x2, x3) = (x1 − x2 + 2x3 ,2x1 + x2 , − x1 − 2 x2 + 2x3 )
i. Verify that T is a linear transformation.
ii. If (a, b, c) is a vector in F
3, what are the conditions on a, b and c that the vector bein the range of T? What is the rank of T?
iii. What are the conditions on a, b and c that the vector (a, b, c) be in the null space of T? What is the nullity of T?
"T:F_3\\rightarrow F_3\\\\\n(x_1,x_2,x_3)\\rightarrow (x_1 \u2212 x_2 + 2x_3 ,2x_1 + x_2 , \u2212 x_1 \u2212 2 x_2 + 2x_3 )"
"=\\begin{bmatrix}1&-1&2\\\\2&1&0\\\\-1&-2&2\\end{bmatrix}\\times\\begin{bmatrix}x_1\\\\x_2\\\\x_3\\end{bmatrix}=AX \\;[let]"
where "A=\\begin{bmatrix}1&-1&2\\\\2&1&0\\\\-1&-2&2\\end{bmatrix},X=\\begin{bmatrix}x_1\\\\x_2\\\\x_3\\end{bmatrix}"
i.e. "T(X)=AX"
(i)
Let "X,Y\\in F_3, c\\in \\mathbb{C}"
"\\therefore T(aX+Y)=A(aX+Y)=aAX+AY=aT(X)+T(Y)"
Hence "T" is a linear transformation.
(ii)
Claim:- "\\{A_1=\\begin{bmatrix}1\\\\2\\\\-1\\end{bmatrix},A_2=\\begin{bmatrix}-1\\\\1\\\\-2\\end{bmatrix}\\}" is a Basis of "Im(T)" .
Proof:-
Any element of "Im(T)" can be expressed by columns of "A \\;\\;i.e. \\;A_1, A_2,A_3"
"\\therefore Im(T)=span(\\{A_1, A_2,A_3\\})"
"A_3=\\frac{2}{3}A_1-\\frac{4}{3}A_2"
"\\therefore A_3\\in span(\\{A_1,A_2\\})"
"\\Rightarrow span(\\{A_1,A_2\\})= span(\\{A_1,A_2,A_3\\})=Im(T)" ...(1)
Now "A_1,A_2" are independent [ as "\\exists no\\;c\\in \\mathbb{C}\\ni A_1=cA_2" ] ...(2)
So, from above two facts, we can conclude that ,
"\\{\\begin{bmatrix}1\\\\2\\\\-1\\end{bmatrix},\\begin{bmatrix}-1\\\\1\\\\-2\\end{bmatrix}\\}" is a Basis of "Im(T)" ...(Proved)
Therefore "\\pmb{rank(T)=dim(Im(T))=2}"
(iii)
Null Space of "\\;T=Null(T)=\\{X\\in F_3 | AX=0\\}"
So,
"\\;\\;\\;\\;\\;AX=0\\\\\n\\Rightarrow \\begin{bmatrix}1&-1&2\\\\2&1&0\\\\-1&-2&2\\end{bmatrix}\\begin{bmatrix}x_1\\\\x_2\\\\x_3\\end{bmatrix}=0\\\\\n\\Rightarrow \\begin{bmatrix}1&0&2\/3\\\\0&1&-4\/3\\\\0&0&0\\end{bmatrix}\\begin{bmatrix}x_1\\\\x_2\\\\x_3\\end{bmatrix}=0\\\\\n\\Rightarrow x_1+\\frac{2x_3}{3}=0, \\;x_2-\\frac{4x_3}{3}=0"
[let "x_3=k"]
"\\Rightarrow X\\in\\{k\\begin{bmatrix}-2\/3\\\\4\/3\\\\1\\end{bmatrix}: k\\in \\mathbb{C}\\}"
"\\therefore Null(T)=\\{k\\begin{bmatrix}-2\/3\\\\4\/3\\\\1\\end{bmatrix}: k\\in \\mathbb{C}\\}"
Clearly Null(T) is generated by 1 element.
Hence, "\\pmb{Nullity\\;\\;of \\;\\;T=dim(Null(T))=1}".
Comments
Leave a comment